Transmisi Harga di Pasar CPO Indonesia: Dampak Kebijakan Ekspor terhadap Kesejahteraan Petani Kecil - Vidiya Rahayu; Marseto Marseto (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Understanding price transmission in crude palm oil (CPO) markets is essential for evaluating the distributional impacts of export taxation on domestic producers. This study investigates price transmission between Indonesia’s ICDX and Malaysia’s MDEX CPO markets while assessing the welfare implications of export duty (BK) and export levy (Levy) on domestic prices and smallholder income. The analysis employs 1,438 daily observations (2019–2024), Johansen cointegration, Granger causality, and a 30-period Variance Decomposition to capture long-run policy effects. Three methodological innovations distinguish this study: the use of high-frequency daily data, extended variance decomposition, and the separate identification of BK and Levy as fiscal instruments with distinct transmission mechanisms. The results confirm a long-run equilibrium between ICDX and MDEX, with unidirectional price leadership from MDEX to ICDX. Export duty affects domestic prices through a netback pricing mechanism, whereas the Levy is transmitted backward along the supply chain, reducing farm-gate Fresh Fruit Bunch (FFB) prices received by smallholders. After 30 periods, external price shocks explain 49.13% of domestic price variation, compared with only 4.03% from BK and Levy combined. The Levy contributes 4.01%, substantially exceeding BK (0.024%), highlighting its greater welfare impact and the importance of long-horizon analysis for evaluating export taxation policies.